PENGARUH PENGGUNAAN MINYAK JAGUNG UNTUK CUTTING FLUID PADA PROSES FACE MILLING TERHADAP KEKASARAN PERMUKAAN PERMUKAAN DAN LAJU KOROSI BAJA KARBON - Widodo, Teguh Dwi; Suwarso, Wahyu Handoyo; Wahyudiono, Arif; Raharjo, Rudianto; Bintarto, Redi; Sasongko, Mega Nur; Darmadi, Djarot Bangun; Setiawan, Yustiza Rahadian (Jurnal Rekayasa Mesin, 2023)
The corrosive coastal environment will result in a high corrosion rate for any equipment installed there. This is due to the constant exposure to saltwater, high humidity levels, and strong winds. Therefore, it is crucial to use corrosion-resistant materials and regularly maintain the equipment to ensure its longevity in such an environment. One method to reduce the rate of corrosion is to pay close attention to the manufacturing parameters of these components, one of which is the face milling process. The aim of this study is investigating the effect of face milling process with different dept of cut using minimum quantity lubrication method with corn oil as a renewable vegetable cutting fluid. In this study AISI 316L stainless steel was face milled using HAAS VF-2 CNC machine. The depth of cut is varied between 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm, and 0.6 mm. The results demonstrated that the greater the depth of cut, the greater the surface roughness value that will be generated. It is resulting in increment in the corrosion rate value.